2023
DOI: 10.1002/ejlt.202200205
|View full text |Cite
|
Sign up to set email alerts
|

Erucic acid ameliorates the lipopolysaccharide‐induced memory deficit in rats through inhibited inflammation cytokines expression/caspase 3/NF‐κB pathways

Abstract: Erucic acid is a single unsaturated fatty acid that falls under the omega‐9 fatty acid family. It was suggested to treat Wistar rats with lipopolysaccharide (LPS)‐induced memory impairment and minimize cognitive impairment. A total of 30 animals were randomized: group I was normally treated group, group II was administered with LPS, group III was treated with LPS along with erucic acid at the dose of 10 mg kg–1 p.o.–1, group IV was treated with LPS along with erucic acid at 20 mg kg–1 p.o.–1 and group V was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The results of this study revealed that neurological disorders had alterations in IL-6 and IL-10 levels, which were reversed by both doses of erucic acid (Tiftik et al, 2021). Additionally, the modulation of cytokines (IL-6 and IL-10) observed in our study aligns with the anti-inflammatory effects of erucic acid reported in previous research (Sayyed et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study revealed that neurological disorders had alterations in IL-6 and IL-10 levels, which were reversed by both doses of erucic acid (Tiftik et al, 2021). Additionally, the modulation of cytokines (IL-6 and IL-10) observed in our study aligns with the anti-inflammatory effects of erucic acid reported in previous research (Sayyed et al, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…They show the ability to inhibit the production of pro-inflammatory cytokines like IL-6 and reduce inflammation, which contributes to the improvement of anxiety and depression symptoms (Bhat & Ara, 2015). Omega-3 fatty acids have antioxidant properties that help in reducing oxidative stress that may positively impact anxiety and depression symptoms (Su et al, 2015;Sayyed et al, 2023). As a result of the administration of erucic acid at both doses, the duration of immobility was reduced in the tail suspension test and forced swim test, indicating an antidepressant effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations